2006
DOI: 10.1128/cvi.13.3.349-355.2006
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous and Exogenous Glucocorticoids in Experimental Enterococcal Infection

Abstract: The potentially protective role of the host adrenal-glucocorticoid response to enterococcal infection was evaluated in an experimental model in which mice were infected intraperitoneally with two distinct Enterococcus faecalis strains (K9 and CP-1). We demonstrated that corticosterone levels in serum and peritoneal-lavage fluid were elevated within 1 hour of infection with either E. faecalis strain. We also demonstrated that adrenalectomized mice generated a more robust localized peritoneal tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Adrenalectomy increased the LPS‐stimulated TNF‐α production by peritoneal macrophages, and this effect was completely abrogated by corticosterone supplementation. This was consistent with data indicating that the expression of pro‐inflammatory cytokines, including TNF‐α, is repressed by glucocorticoids (Tuckermann et al 2005) and that adrenalectomized mice generate a more robust localized peritoneal TNF‐α response to Enterococcus faecalis infection, which can be completely suppressed by prior treatment with dexamethasone (Papasian et al 2006). It should be noted that adrenal glucocorticoid withdrawal may indirectly influence, at least partly, TNF‐α production through the stimulation of macrophage corticotrophin‐releasing hormone synthesis and release (Robinson et al 1988; Karalis et al 1991; Agelaki et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Adrenalectomy increased the LPS‐stimulated TNF‐α production by peritoneal macrophages, and this effect was completely abrogated by corticosterone supplementation. This was consistent with data indicating that the expression of pro‐inflammatory cytokines, including TNF‐α, is repressed by glucocorticoids (Tuckermann et al 2005) and that adrenalectomized mice generate a more robust localized peritoneal TNF‐α response to Enterococcus faecalis infection, which can be completely suppressed by prior treatment with dexamethasone (Papasian et al 2006). It should be noted that adrenal glucocorticoid withdrawal may indirectly influence, at least partly, TNF‐α production through the stimulation of macrophage corticotrophin‐releasing hormone synthesis and release (Robinson et al 1988; Karalis et al 1991; Agelaki et al 2002).…”
Section: Discussionsupporting
confidence: 91%
“…E. faecalis AG5 can increase both long- and short-chain fatty acids in the host, which might indirectly affect the nervous system through an indirect fashion [ 228 ]. One report found that infection of mice with pathogenic E. faecalis strains, K9 and CP-1 , increased corticosterone in an acute manner, suggesting that E. faecalis can alter glucocorticoid signaling in the host [ 229 ]. Clinically, E. faecalis was present in 89.3% of healthy controls, whereas only in 58.3% of neurodevelopmental disorders, 58.3% of mixed specific developmental disorders, and 55.6% of expressive and receptive language disorder [ 230 ].…”
Section: Introductionmentioning
confidence: 99%